Humanoid Introspection: A Practical Approach. (15th May 2013) - Infantino, Ignazio; Pilato, Giovanni; Rizzo, Riccardo; Vella, Filippo
Abstract We describe an approach to robot introspection based on self observation and communication. Self observation is what the robot should do in order to build, represent and understand its internal state. It is necessary to translate the state representation in order to build a suitable input to an ontology that supplies the meaning of the internal state. The ontology supports the linguistic level that is used to communicate information about the robot state to the human user.